PERSEPSI GURU SEKOLAH DASAR TERHADAP PENGGUNAAN MEDIA DIGITAL DALAM MENINGKATKAN LITERASI MEMBACA SISWA - Elisabeth Febryanti Mele Tena; Juliana Asbanu; Haenael, Junetry Olivia; Ronald Meyrjhon Ndolu; Adam Bol Nifu Benu; Habibi Musa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine elementary school teachers’ perceptions of the use of digital media in improving students’ reading literacy. The integration of digital technology in learning raises various concerns related to teachers’ preparedness, the availability of digital resources, and the alignment of digital media with the goals of reading instruction. Therefore, this research focuses on identifying teachers’ attitudes, experiences, and expectations in utilizing digital media in reading instruction at the elementary level. The research method used is descriptive quantitative, with questionnaires serving as the primary data collection instrument to obtain information regarding teachers’ perceptions and the factors that influence them. The questionnaire is designed to explore aspects such as the usefulness of digital media, ease of use, availability of digital infrastructure, and the challenges that teachers may encounter.